Socioeconomic differences in animal food consumption: Education rather than income makes a difference - Klink, Urte; Mata, Jutta; Frank, Roland; Schüz, Benjamin (Frontiers in Nutrition, 2022)
Background/aims Evidence points toward more sustainable and health-conscious dietary behaviors among individuals with higher socioeconomic status. However, these differences vary considerably depending on which indicator of socioeconomic status is examined. Here, we present a systematic parallel investigation of multiple indicators of socioeconomic status as predictors of animal food consumption frequency and selected food-related behaviors in Germany. Methods Data from the German subsample of two large representative European consumer studies (Study 1 n = 1,954; Study 2 n = 2,045) was used. We assessed the associations between the socioeconomic indicators income, current occupation as well as education and consumption frequency of animal foods and selected food-related behaviors in separate ordinal logistic regressions. Results Individuals with higher educational attainment engaged in more sustainable and health-conscious dietary behaviors, indicated by significant associations between educational attainment and the consumption frequency of animal foods. Low- and middle-income participants consumed processed meat more frequently (Study 1 only; medium income: OR 1.5, CI 1.09–2.05, p = 0.012; low income: OR 1.43, CI 1.01–2.05, p = 0.047) and fish less frequently (Study 2 only; medium income: OR 0.76, CI 0.59–0.97, p = 0.026; low income: OR 0.061, CI 0.46–0.82, p < 0.001) than participants with high income. Current occupation did not predict the consumption of animal foods or food-related behaviors. Intake frequency of animal-based foods indicates that most participants exceeded national dietary recommendations for meat and processed meat and remained below recommendations for fish and dairy/eggs intake. Conclusion Educational attainment appears to be the strongest and most consistent socioeconomic indicator of sustainable dietary choices in Germany based on current large, representative studies. Future efforts should be directed toward education interventions about nutrition and interpretation of food labels to compensate for differences in dietary behavior among groups with different levels of education.